(untitled) (Studia austriaca, 2014)
The crisis of substance and the difficulty of making decisions are fundamental cores in Musil’s conception of the subject. In The Man Without Qualities subjectivity is the consequence of a precise ontology which deconstructs, in the manner of Mach, the very structure of reality. But Musil is not Mach, and he does not merely translate his categories into literature. There is a philosophical originality in his thought revealing a design in which the dissolution of substance and the unsaveability of the ego turn into the development of a paralysing “sense of possibility”. This essay restores an image of Musil fascinated by the theme of the undecidable, but also an acute critic of all the forms of ethical-political decisionism.